Influence of weight status at 2 years on memory performance at 4-5 years of age - Simone de Kácia Wendt; Bruna Constantino; Edimari A. Wendt; Marco F. Mastroeni (Taylor & Francis Group, 2019)
Background: Memory performance is a cognitive function that is affected by environmental, genetic and socioeconomic factors, as well as by weight status. Aim: To evaluate the association of weight status at 2 years of age with the memory performance of children at 4-5 years of age. Subjects and methods: A cross-sectional study that used baseline data (2012) and data from two follow-up periods (2014 and 2016) of the PREDI Cohort Study. Participants were mother-child pairs 4-5 years after delivery who were seen between July 2016 and August 2017. The children's memory performance was evaluated individually using a validated Brazilian instrument. Results: Of the 203 children included in the study, 117 (57.6%), 52 (25.6%) and 34 (16.8%) had low, moderate and high memory performance, respectively. After adjusting for potential confounders, children with a BMI > 85th percentile had 3.33-times higher odds of exhibiting lower memory performance at 4-5 years of age than those with a BMI ≤ 85th percentile. In addition to the children's BMI at 2 years of age, mother's education was another independent determinant of children's memory performance. There was a progressive increase in the odds of children having lower memory performance at 4-5 years of age as the mother's education decreased. Conclusion: Primary prevention of overweight and management of cognitive functions may be important strategies to improve the cognitive development of children in the future.